Sharia Fintech: Opportunities and Challenges in Indonesia - Agustina, Refi; Faizah, Fita Nurotul (Journal of Islamic Economics (JoIE), 2023)
Introduction: The rapid development of technology will certainly have a direct impact on the economic aspects of life. The presence of financial technology (fintech) will make it easier to obtain financing in a relatively fast time and easy to use capital. Fintech in Indonesia has given rise to a new innovation, namely sharia fintech. This study aims to determine the potential and challenges of fintech as an economic development effort correlated with sharia principles in encouraging a country's economic growth rate. Method: This study uses a qualitative approach of qualitative descriptive method because this research will explain the facts or symptoms that appear in the development of Islamic fintech in Indonesia. This research uses secondary data collection in the form of news and research journals on the phenomenon of Islamic fintech in Indonesia. Result: The results showed that currently the development of fintech platforms is growing rapidly from 2015. The presence of sharia fintech is a great. Based on OJK data, in 2021 the contribution of the Indonesian fintech industry has reached IDR272.4 trillion. This will certainly be an opportunity for the financial industry, especially sharia. Conclusion: To revolutionize conventional activities into sharia-based digital product service innovations to facilitate the community.